Long-Term Lime and Phosphogypsum Amended-Soils Alleviates the Field Drought Effects on Carbon and Antioxidative Metabolism of Maize by Improving Soil Fertility and Root Growth - Bossolani, João William; Crusciol, Carlos Alexandre Costa; Garcia, Ariani; Moretti, Luiz Gustavo; Portugal, José Roberto; Rodrigues, Vitor Alves; Fonseca, Mariley de Cássia da; Calonego, Juliano Carlos; Caires, Eduardo Fávero; Amado, Telmo Jorge Carneiro; Reis, André Rodrigues dos (Frontiers in Plant Science, 2021)
Long-term surface application of lime (L) and/or phosphogypsum (PG) in no-till (NT) systems can improve plant growth and physiological and biochemical processes. Although numerous studies have examined the effects of L on biomass and plant growth, comprehensive evaluations of the effects of this practice on net CO2 assimilation, antioxidant enzyme activities and sucrose synthesis are lacking. Accordingly, this study examined the effects of long-term surface applications of L and PG on soil fertility and the resulting impacts on root growth, plant nutrition, photosynthesis, carbon and antioxidant metabolism, and grain yield of maize established in a dry winter region. At the study site, the last soil amendment occurred in 2016, with the following four treatments: control (no soil amendments), L (13 Mg ha-1), PG (10 Mg ha-1), and L and PG combined (LPG). The long-term effects of surface liming included reduced soil acidity and increased the availability of P, Ca2+ and Mg2+ throughout the soil profile. Combining L with PG strengthened these effects and also increased SO42--S. Amendment with LPG increased root development at greater depths and improved maize plant nutrition. These combined effects increased the concentrations of photosynthetic pigments and gas exchange even under low water availability. Furthermore, the activities of Rubisco, sucrose synthase and antioxidative enzymes were improved, thereby reducing oxidative stress. These improvements in the physiological performance of maize plants led to higher grain yield. Overall, the findings support combining soil amendments as an important strategy to increase soil fertility and ensure crop yield in dry regions.